1998
DOI: 10.1038/bjc.1998.167
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactivity between Candida albicans and human ovarian carcinoma as revealed by monoclonal antibodies PA10F and C6

Abstract: Summary Antibodies against Candida albicans antigenic determinants have been reported to cross-react with human tumour cells. We have found that two monoclonal antibodies, C6 and PAl OF, developed at our laboratory against C. albicans antigenic determinants, cross-react with human ovarian cancer on Western blots and immunohistochemistry. We have subsequently used one of them, PA1OF, to test by means of immunohistochemistry a series of 37 human ovarian carcinomas. Out of 37 tumours, 25 (67.6%) expressed the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…4 In the course of the investigation leading to the recognition that Nup88 is overexpressed in tumor cells, we also developed a polyclonal antibody against Nup88, which has been used in further studies. In them, it has been shown that Nup88 is overexpressed in virtually all tumor tissues 5 and, furthermore, that this overexpression is linked to a higher aggressiveness of colorectal carcinoma 6 and to enhanced metastatic potential of melanoma cells.…”
mentioning
confidence: 99%
“…4 In the course of the investigation leading to the recognition that Nup88 is overexpressed in tumor cells, we also developed a polyclonal antibody against Nup88, which has been used in further studies. In them, it has been shown that Nup88 is overexpressed in virtually all tumor tissues 5 and, furthermore, that this overexpression is linked to a higher aggressiveness of colorectal carcinoma 6 and to enhanced metastatic potential of melanoma cells.…”
mentioning
confidence: 99%
“…A monoclonal antibody raised against Candida albicans unexpectedly cross-reacted with human Nup88 [17] , leading to the discovery of Nup88 overexpression in a broad spectrum of neoplasias, including carcinomas, sarcomas, lymphomas and mesotheliomas [18] . Immunoblotting several lung carcinoma samples demonstrated that Nup88 expression did not correlate with a concomitant overexpression of its interacting partner Nup214, suggesting selective nucleoporin dysregulation [18] .…”
Section: Regulation Of Nucleoporin and Nucleophosminmentioning
confidence: 99%
“…The immunohistochemical procedure has been extensively described elsewhere (Schneider et al, 1998;Martínez et al, 1999;Gould et al, 2000).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…We could not study the mouse embryo with our mouse-derived monoclonal antibodies for obvious reasons, but the chick embryo instead did not show any disturbing background reactivity during preliminary studies with the different monoclonal antibodies derived from related hybrido-mas developed against yeast antigens. One of them, C7, closely related to the C6 antibody which we previously reported (Schneider et al, 1998), showed the best pattern of reactivity both in human cancer and in the chick embryo. Monoclonal antibody C7 is an IgM directed against an epitope expressed on a mannoprotein of >200 kDa from a variety of Candida species which has been shown to exert direct candidacidal activity (Moragues et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation